Kekuatan Hukum Hasil Mediasi dalam Sengketa Asuransi di BPSK: Tinjauan dari Undang-Undang Perlindungan Konsumen - Dahlan Sitohang; Maria Helena Sri Rahayu (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Insurance is a service designed to prevent or mitigate various potential risks. The Consumer Dispute Settlement Agency (BPSK) is authorized to resolve consumer disputes through three alternative methods: arbitration, conciliation, and mediation. This study aims to analyze the legal force of mediation outcomes and to identify and examine the obstacles encountered in the implementation of insurance dispute resolution through BPSK mediation. This research employs a normative legal method with a statutory approach through literature review. The analysis is conducted qualitatively based on legal regulations and principles. Data is sourced from primary, secondary, and tertiary materials, and the process consists of three stages: formulation, analysis, and conclusion. The findings indicate that although BPSK’s authority is limited, its decisions are final and binding, and mediation agreements remain legally valid. If no objection is filed, the agreement must be implemented, with criminal consequences for non-compliance. However, the effectiveness of consumer dispute resolution remains hindered by weak legal force, limited regulatory framework, institutional capacity constraints, and potential external intervention.